Systems-Based Geri-Anatomy Curriculum - Mariana Dangiolo; Andrea Berry; Julia Heizmann; Scott Furer; Monica Doctor (Association of American Medical Colleges, 2016)
Abstract Introduction The Systems-Based Geri-Anatomy Curriculum is a peer-facilitated, experiential program that is designed to orient preclinical medical students to the introductory set of knowledge and skills needed to meet the special clinical needs of the aging population. Through a series of 30-minute, one introductory/surface anatomy and six system-specific sessions, both first-year medical students and their second-year mentors benefit from the clinical correlations that are made as they learn how their "first patients" may have lived and died. Methods The materials presented will be most useful for anatomy course directors or geriatric curriculum leaders and can be used as a series of sessions (as utilized by the authors) or individually in the anatomy lab. When implemented in its entirety, the program requires approximately a 3.5-hour commitment. Additionally, the facilitator training for second-year students generally takes 1 hour. The resource includes all handouts and visual aids for each Geri-Anatomy session as well as a facilitator training PowerPoint presentation for second-year mentors. Results The Geri-Anatomy curriculum has been delivered to five cohorts of medical students over the past 5 years. While the quantitative pre- and posttest surveys (about 35 students) demonstrated no statistically significant findings, the qualitative data (from both surveys and verbal feedback) and test data have indicated otherwise. Over 90% of the students who answered the National Board of Medical Examiners-style questions (also submitted with this resource) answered them correctly. Discussion The qualitative data have demonstrated that the first-year medical students have a greater appreciation for the chronic disease process in older patients and have gained knowledge and experience in thinking about how these conditions impact activities of daily living and instrumental activities of daily living.